Ability of physiotherapists to undertake evidence-based practice steps: a scoping review. Issue 1 (March 2016) - Condon, C.; McGrane, N.; Mockler, D.; Stokes, E.
Abstract: Background: Evidence-based practice (EBP) is promoted to ensure quality of care. However, analysis of the skill of physiotherapists in undertaking the steps of EBP, or the impact of EBP on the work of physiotherapists is limited. Objectives: To conduct a scoping review into physiotherapists performing the steps of EBP. Data source: Literature concerning the skill of physiotherapists in EBP between 1990 and June 2013 was searched using AMED, Academic Search Complete, CINAHL, PubMed, ERIC, PEDRO and EMBASE databases. Study selection: Twenty-five studies (six qualitative, one mixed methods and 18 quantitative) were selected. Data extraction and synthesis: Quantitative and qualitative data were extracted using two appraisal tools to analyse each of the five steps of EBP. Results: Limited evidence exists to show that physiotherapists undertake the full EBP process. Despite formulating clinical questions and acquiring literature-based evidence, the drivers for conducting literature or evidence searches have not been clarified. The critical appraisal step was mainly assessed in the form of recognition of statistical terms. Only examples of guideline usage support the reflective final assessment step. Physiotherapists report using their peers and other trusted sources in preference to literature, primarily due to time but also due to divergence between the literature-based evidence and other evidence that they use and value (tacit knowledge). A positive impact of EBP on patient outcomes is lacking. Conclusions: Understanding the information needs of physiotherapists may be necessary before adoption of the EBP process. The use of professional networks may offer a better means to identify knowledge gaps and translate acquired knowledge into practice, rather than focusing on individual skills in EBP.